O paradigma de desenvolvimento de sistemas baseados em regras aplicadas na composição de serviços em uma arquitetura orientada à serviço - Dias, Claudio Otoni Milan (2010)
This work has as objective to study a method that enables integration between business process and business rules processing that attend the present enterprise system development requirements. Development that enables the improvements and system maintance by knowledge manager, business analist for instance. Without code modification, just diagrams and domain specific languages. Based on an service oriented development architecture, this integration between process and business rules will be studied in a SOA platform, over an Enterprise Service Buss (ESB), where there are process excecution inside BPEL layer and business rules being executed in BRE layer. The way that this tecnology could be unified still being a chalenge faced on this work, explore one integration possibility between process and rules into an enterprise system will be the main objective of this work